A Review on Recent Trends in Green Synthesis of Gold Nanoparticles for Tuberculosis - Arti Gupta; Sonia Pandey; Jitendra Singh Yadav (Tabriz University of Medical Sciences, 2021)
Tuberculosis (TB) is a contagious disease that has affected mankind. The anti-TB treatment has been used from ancient times to control symptoms of this disease but these medications produced some serious side effects. Herbal products have been successfully used for the treatment of TB. Gold is the most biocompatible metal among all available for biomedical purposes so Gold nanoparticles (GNPs) have sought attention as an attractive biosynthesized drug to be studied in recent years for bioscience research. GNPs are used as better catalysts and due to unique small size, physical resemblance to physiological molecules, biocompatibility and non-cytotoxicity extensively used for various applications including drug and gene delivery. Greenly synthesized GNPs have much more potential in different fields because phytoconstituents used in GNP synthesis itself act as reducing and capping agents and produced more stabilized GNPs. This review is devoted to a discussion on GNPs synthesis with herbs for TB. The main focus is on the role of the natural plant bio-molecules involved in the bioreduction of metal salts during the GNPs synthesis with phytoconstituents used as antitubercular agents.